2022
DOI: 10.1021/acs.macromol.1c02538
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Epoxy Vitrimers Based on Transesterification Internally Activated by an α–CF3 Group

Abstract: Vitrimers are polymer networks in which associative exchange reactions can take place under specific conditions, thus conferring reprocessability to the insoluble materials. Recently, catalyst-free vitrimers have emerged as a new generation of vitrimers able to overcome potential leaching, ageing and sintering issues of catalysts and to ensure the preservation of the vitrimer properties after numerous reshaping processes. Here, a catalyst-free epoxy vitrimer featuring α-CF3-substituted ester functions is repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 73 publications
0
63
0
Order By: Relevance
“…Our group has recently reported polyester vitrimers featuring two fluorine atoms in α‐position the ester functions, which indeed can be reshaped under mild conditions without catalyst and thus confirmed the above‐mentioned F‐effect hypothesis [17] . Additional work has also revealed that the reshaping of transesterification vitrimers can be accelerated by the introduction of an α‐CF 3 group (fluorine atoms in β‐position), which was supported by DFT calculations on a model transesterification reaction [18] . Following those initial investigations, we have conducted more extensive DFT calculations in order to quantitatively assess the effect of neighbouring fluorinated groups on the transesterification reaction rate.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Our group has recently reported polyester vitrimers featuring two fluorine atoms in α‐position the ester functions, which indeed can be reshaped under mild conditions without catalyst and thus confirmed the above‐mentioned F‐effect hypothesis [17] . Additional work has also revealed that the reshaping of transesterification vitrimers can be accelerated by the introduction of an α‐CF 3 group (fluorine atoms in β‐position), which was supported by DFT calculations on a model transesterification reaction [18] . Following those initial investigations, we have conducted more extensive DFT calculations in order to quantitatively assess the effect of neighbouring fluorinated groups on the transesterification reaction rate.…”
Section: Introductionmentioning
confidence: 68%
“…Following the recently reported acceleration for the reshaping process in transesterification vitrimers upon introduction of F atoms at the ester α [17] and β [18] positions, it was of interest to use the computational approach to understand the origin of this effect and to predict how to possibly further improve the transesterification rate.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscosity of these polymeric materials gradually decreases with temperature as the rate of intermolecular transesterification increases following the Arrhenius law, which is a typical property of vitreous silica; hence, these polymers are called vitrimers [14]. This pioneering work on vitrimers and the subsequent reports have motivated many other research groups to design and synthesise various vitrimers using not only transesterification reactions [15][16][17][18] but also other dynamic covalent chemical processes, such as transaminations [19][20][21], transalkylations [22][23][24][25][26], siloxane-silanol exchange [27,28], olefin-metathesis exchange [1,29], disulfide exchange [30][31][32], and conjugate addition-elimination reactions [33]. The studies of such bond reorganization allows us to gain mechanistic insights [1] and specific applications such as shape memory behaviour [27].…”
Section: Introductionmentioning
confidence: 99%